Synaptic behaviour in ferroelectric epitaxial rhombohedral Hf0.5Zr0.5O2 thin films. Issue 4 (1st December 2022) - Wei, Yingfen; Vats, Gaurav; Noheda, Beatriz
Abstract: The discovery of ferroelectricity in HfO2 -based thin films brings tremendous opportunities for emerging ferroelectric memories as well as for synaptic devices. The origin of ferroelectricity in this material is widely attributed to the presence of a polar orthorhombic phase. However, a new ferroelectric rhombohedral phase displaying large polarization with no need of pre-cycling, has more recently been reported in epitaxial Hf0.5 Zr0.5 O2 (HZO). In this work, the switching mechanism of the rhombohedral phase of HZO films is characterized by a two-stage process. In addition, the synaptic behaviour of this phase is presented, comparing it with previous reports on orthorhombic or non-epitaxial films. Unexpected similarities have been found between these structurally distinct systems. Even though the epitaxial films present a larger coercive field, the ration between the activation field for intrinsic polarization switching and the coercive field ( F a / E c ) has been found to be close to 2, in agreement with that reported for other hafnia samples. This is about 5 times smaller than in most other ferroelectrics, confirming this characteristic as a unique feature of hafnia-based ferroelectrics.